Particle Swarm Optimization Algorithm Based Optimization of Steam Turbine Generator and Gas Turbine Generator at Pt. Sriwidjaja Fertilizer - Taufik Barlian; Azizul Muttaqin; Israa Al_barazanchi; Irfan Ahmad; Wiwin A. Oktaviani (Journal of Telecommunication Control and Intelligent System, 2021)
Electricity needs at PT. PUSRI is currently generated by four main generating units in the form of a Gas Turbine Generator (GTG). The three power plants are PUSRI-II (2006-J), PUSRI-III (3006-J), PUSRI-IV (4006-J) each with a capacity of 21.588kVA. PUSRI-IB (5006-J) with a capacity of 26.65kVA. Each unit is operated in parallel via a 13.8 kV syncronizing bus. However, for reasons of generator efficiency at PT. PUSRI with gas costs that are quite expensive will gradually be replaced by a Steam Turbine Generator – Coal (STG-BB) generator. The contribution of this paper uses the Particle Swarm Optimization (PSO) algorithm to find the optimum output (MW) from each generating unit. The results of the PSO calculation provide a better solution performance compared to the real system with the same generated power variation, namely 34.25 (MW) to 37.63 (MW). The cost savings obtained from the comparison between the PSO method and the real output of the system is Rp. 5,180.509 at load 34.25 (MW) and Rp. 6,416.864 at 37.63(MW) load.